2015
DOI: 10.1186/s13256-015-0612-x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous dysplasia of the temporal bone secondary to ear surgery: a case report

Abstract: IntroductionIn this report, we describe the clinical course, diagnostic features and management of a patient with fibrous dysplasia of the temporal bone 7 years after middle ear surgery on the same side.Case presentationA 16-year-old Caucasian girl presented to our hospital with a growing bone lesion in the roof of the left temporal bone. She had undergone a previous tympanoplasty at 7 years of age because of a cholesteatoma. At the time of that first surgery, no radiological or histological signs indicated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
6

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
7
0
6
Order By: Relevance
“…Pardo-Maza et al [ 11 ] described a case in which temporal bone FD developed 7 years after middle ear surgery involving cholesteatoma removal. This case emphasizes the importance of close follow-up after otologic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pardo-Maza et al [ 11 ] described a case in which temporal bone FD developed 7 years after middle ear surgery involving cholesteatoma removal. This case emphasizes the importance of close follow-up after otologic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies revealed a somatic activating mutation within the GNAS1 gene located on chromosome 20 [ 6 , 10 ]. In 2015, Pardo-Maza et al [ 11 ] described a case of FD in which the pathologic process was suggested to be a late complication of temporal bone cholesteatoma surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 30 ] Symptoms of aggressive lesions include worsening headaches, severe edema, mass effect, compromised vision, compromised hearing, and altered cosmetic appearance. [ 2 12 16 18 25 ] Our case offers 18 years of insight into the natural history of cranial FD with worsening mass effect and headaches manifesting from a growing lesion in the frontotemporal area.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to our patient, several cases reported in the literature have involved monthly growth with worsening symptoms appearing closer to surgical intervention. [ 12 16 18 25 ] One interesting aspect of this particular case is the aggressive and invasive nature of the lesion observed intraoperatively, in conjunction with growth of the lesion over 18 years. Over years, the patient elected to monitor the lesion radiographically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation